Some common pollutants in groundwater utilized in water-supply systems at São Paulo state, Brazil - Bonotto, Daniel Marcos [UNESP] (My University, 2012)
The water cycle describes the processes that drive the movement of water throughout the hydrosphere, whilst a reservoir represents the water contained in different steps within the cycle. The largest reservoir is the collection of oceans, accounting for 97% of the Earth's water. The next largest quantity (2%) is stored in solid form in the ice caps and glaciers, whereas the third reservoir in size (0.7%) is groundwater. São Paulo is the most populous Brazilian state, comprising circa 40 million inhabitants distributed over 645 municipalities. It has the highest number of industries and economic production, reaching 31% of the Brazilian GDP-gross domestic product. Despite the vigorous industrial production that includes high technology goods, the state also is well developed in agriculture and cattle breeding. This advanced stage of agricultural and industrial growth causes to São Paulo State an accentuated use of groundwater resources in water-supply systems. As a consequence, there is a great diversity of problems related to the use of these resources due to the interaction between the society and the environment. Additionally, there is a general relationship between mineral composition of the natural water and that of the solid minerals with which the water has been in contact. This relationship may be comparatively simple and uncomplicated, as in the case of an aquifer receiving direct recharge by rainfall and from which water is discharged without contacting any other aquifer or other water. Or the situation may be rendered very complex by influence of one or more interconnected aquifers of different composition, mixing of unlike waters, chemical reactions such as base-exchange, adsorption of dissolved ions, and other factors like anthropogenic inputs. Thus, during the water movement according to the hydrologic cycle, it may be verified water pollution, i.e. contamination of water by undesirable foreign matter. Pollution comes in many forms, some conventional and others toxic, thus, impacting the groundwater. This chapter reports the presence of some chemicals in groundwaters utilized in water-supply systems at São Paulo State, Brazil. Particular attention will be directed for describing the importance of nitrate and fluoride on the pollution of groundwaters that are often used for human consumption. © 2012 by Nova Science Publishers, Inc. All rights reserved.